US agricultural policy in disarray: Title I programs - Goodwin, Barry K. (2018)
Barry K. Goodwin BOOK LAUNCH Agricultural Policy in Disarray: Reforming the Farm Bill Co-Hosted by IFPRI and American Enterprise Institute DEC 12, 2018 - 12:15 PM TO 01:45 PM EST